Intencionalidades e saberes provisórios da criança: vivências epistemológicas de itinerários Reggio Emília nos anos iniciais do Ensino Fundamental - Corrêa, Claudia Aparecida da Silva (2023)
The present study, considering the curriculum based on Reggio Emilia Schools (Italy) and its approach to Early Childhood Education, seeks to analyze, through an investigative process, the possible inspirations of some Reggian itineraries and experiences of this project, also to be developed in the Early Years of Elementary Education. It aims to think about composing learning itineraries in the Elementary School curriculum based on the Reggio Emília approach, seeking to overcome the rupture in the passage from the infantile cycle to the fundamental one. The Reggian approach presents itself to Early Childhood Education as a unique system with philosophical assumptions, curriculum and pedagogy, which is based on collectivity and the idea that children are capable of conducting their own learning. In order to analyze the applicability of this idea, during the process, exploratory activities based on Reggio Emilia were carried out, through bibliographic research, field research and experiences. The research was carried out from a qualitative perspective, through bibliographical and documentary research and data collection was based on semistructured interviews and the application of proposed activities based on Regian principles in the scenario under study. of the research was the private educational institution “Escola Oficina Pindorama” and had the participation of teachers and students. It is based on Dewey, Feldmann, Formosinho, Gardner, Loris Malaguzzi, Paulo Freire, Rinaldi, among others. Among the results obtained from the reports of families and school staff prove that epistemological experiences are relevant premises to compose the curriculum of the Early Years of Elementary Education with a wealth of benefits for scientific continuity in education. We believe that the research brought contributions by tracing new paths for the construction of subjective, transversal and more significant curricula that move from Intentionality to Children's Provisional Knowledge